THE ADESSIVE CASE IN POLISH: A COGNITIVE PERSPECTIVE ON SOME LOCATIVE PREPOSITIONS - Kokorniak, Iwona (Versita Ltd., de Gruyter, 2009)
The aim of this paper is to show that what is considered in Polish as one heterogeneous LOCA- TIVE case in the “formal” approach only on the surface seems rather complex and appears to lack any natural order. Due to the limited size of the paper, focus will be laid only on one locative case, the ADESSIVE, representing the static external locative, expressing different aspects of a relationship outside an entity and describing the “location ‘on top of’ or ‘near’, ‘owner’ or ‘in- strument’ by means of which an action is performed” (Karlsson 1999: 115). It has no single lin- guistic equivalent in Polish; instead it is represented by several prepositions, such as na + LOC ‘on’, przy + LOC ‘by’ and u + GEN ‘at’, etc., reflecting different aspects of proximity and coin- cidence in space. Taking just the case of the ADESSIVE relation, data observations based on the IPI PAN Corpus of Polish allow us to claim that although each preposition is responsible for a different aspect of the external spatial relation, they complement one another and are related in a family resemblance fashion, expressing an adessive relation.
Keywords: prepositions; adessive; locative; proximity; coincidence